2023
DOI: 10.3389/fneur.2023.1195923
|View full text |Cite
|
Sign up to set email alerts
|

Detection of brain regions responsible for chronic pain in osteoarthritis: an fMRI-based neuroimaging study using deep learning

Abstract: IntroductionChronic pain is a multifaceted condition that has yet to be fully comprehended. It is frequently linked with a range of disorders, particularly osteoarthritis (OA), which arises from the progressive deterioration of the protective cartilage that cushions the bone endings over time.MethodsIn this paper, we examine the impact of chronic pain on the brain using advanced deep learning (DL) algorithms that leverage resting-state functional magnetic resonance imaging (fMRI) data from both OA pain patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…Pain is a common clinical symptom of OA [ 1 , 2 ]. We found that the thresholds of MWT and TWL were decreased significantly in OA model, whereas Rehmannia treatment significantly increased the pain tolerance threshold.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pain is a common clinical symptom of OA [ 1 , 2 ]. We found that the thresholds of MWT and TWL were decreased significantly in OA model, whereas Rehmannia treatment significantly increased the pain tolerance threshold.…”
Section: Discussionmentioning
confidence: 99%
“…Osteoarthritis (OA) is a chronic joint disease characterized primarily by chronic pain and involving all joint tissues, including degeneration of cartilage and meniscus, inflammation and fibrosis of synovium and infrapatellar fat pad, as well as remodeling of subchondral bone [ 1 , 2 ]. Due to the complexity of pain causing factors and the unclear mechanism of pain transmission, effective analgesia has become a key issue that troubles clinical treatment [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Proposed through a meticulous theoretical framework, this model's architecture is intricately designed to address the complex challenges of lane identification and precise parking spot detection in dynamic seaport environments. Drawing upon the foundational concepts of CNN, a cornerstone in AI renowned for its ability to extract intricate hierarchical features from visual data sources [35,36], our model is shaped in the realm of theoretical possibility.…”
Section: Model Development: Architectural Excellence For Lane Identif...mentioning
confidence: 99%
“…Its early detection is often impeded by subtle radiographic markers and the variability in disease progression [25,28]. Leveraging deep learning for classifying KOA [30][31][32][33][34] depends heavily on the availability of diverse and extensive datasets. However, obtaining such datasets is challenging, constrained by patient privacy considerations [35,36], data collection restrictions, and the inherent nature of OA.…”
Section: Introductionmentioning
confidence: 99%